Chaenomelis fructus inhibits osteoclast differentiation by suppressing NFATc1 expression and prevents ovariectomy-induced osteoporosis - Kim, Minsun (BMC Complement Med Ther, 2020)
BACKGROUND: Osteoporosis is related to the number and activity of osteoclasts. The goal of the present study was to demonstrate the effect of Chaenomelis Fructus (CF) on osteoclastogenesis and its mechanism of bone loss prevention in an OVX-induced osteoporosis model. METHODS: Osteoclasts were induced by RANKL in RAW 264.7 cells. TRAP assay was performed to measure the inhibitory effect of CF on osteoclast differentiation. Then, Expression of nuclear factor of activated T-cells (NFATc1), c-Fos which are essential transcription factors in osteoclastogenesis were detected using western blot and RT-PCR. The osteoclast-related markers were measured by RT-PCR. Moreover, the ability of CF to inhibit bone loss was researched by ovariectomized (OVX)-induced osteoporosis. RESULTS: Cell experiments showed that CF inhibited osteoclast differentiation and its function. Immunoblot analyses demonstrated that CF suppressed osteoclastogenesis through the NFATc1 and c-Fos signaling pathways. RT-PCR determined that CF inhibited osteoclast-related markers, such as tartrate-resistant acid phosphatase (TRAP), cathepsin K (CTK), osteoclast-associated immunoglobulin-like receptor (OSCAR), ATPase H+ Transporting V0 Subunit D2 (ATP6v0d2) and carbonic anhydrase II (CA2). In animal experiments, CF showed an inhibitory effect on bone density reduction through OVX. Hematoxylin and eosin (H&E) staining analysis data showed that CF inhibited OVX-induced trabecular area loss. TRAP staining and immunohistochemical staining analysis data showed that CF displayed an inhibitory effect on osteoclast differentiation through NFATc1 inhibition in femoral tissue. CONCLUSION: Based on the results of in vivo and in vitro experiments, CF inhibited the RANKL-induced osteoclasts differentiation and its function and effectively ameliorated OVX-induced osteoporosis rats.